ANALISIS TINGKAT KEPUASAN PASIEN DI KLINIK PRATAMA SALBIYANA DENGAN ALGORITMA C4.5 - Riki Hamdani; Sriani Sriani; Ali Darta (Smart Education, 2024)
Abstract: Each Clinic has its own management information system. Several aspects of the Clinic management information system at the Pratama Salbiyana Clinic, namely aspects of registration, nurses, doctors, facilities, cleanliness, convenience, administration and finance. The management information system for Pratama Salbiyana Clinic is an important component in realizing quality improvement efforts. The management information system for Pratama Salbiyana Clinic in general aims to integrate information systems from various subsystems and process the information needed for decision making. The management of Pratama Salbiyana Clinic requires effective and efficient management. The number of patients seeking treatment at the Salbiyana Primary Clinic, especially in each polyclinic, will fluctuate every month for the period from January 2021 to December 2021. The quality of the Salbiyana Primary Clinic must be maintained so that it can provide the best service to help achieve goals and improve the quality of life of patients. Patient satisfaction is very important in assessing the quality of services provided by hospitals to their patients. An accurate level of patient satisfaction is needed in efforts to improve the quality of health services. Therefore, measuring the level of patient satisfaction needs to be done regularly, regularly, accurately and continuously. In this case the researcher wants to use classification data mining to predict patient satisfaction with the management information system of Pratama Salbiyana Clinic. Data collection techniques were carried out by observation, literature studies and interviews. Â Keywords: C4.5 algorith; data mining; patient satisfaction level Abstrak: Setiap Klinik memiliki sistem informasi manajemen masing-masing. Beberapa aspek sistem informasi manajemen Klinik pada Klinik Pratama Salbiyana yakni aspek pendaftaran, perawat, dokter, fasilitias, kebersihan, kenyamanan, administrasi dan keuangan.Â Sistem informasi manajemen Klinik Pratama Salbiyana merupakan salah satu komponen yang penting dalam mewujudkan upaya peningkatan mutu. Sistem informasi manajemen Klinik Pratama Salbiyana secara umum bertujuan untuk mengintegrasikan sistem informasi dari berbagai subsistem dan mengolah informasi yang diperlukan sebagai pengambilan keputusan. Manajemen Klinik Pratama Salbiyana menghendaki pengelolaan yang efektif dan efesien. Jumlah pasien yang berobat di Klinik Pratama Salbiyana khususnya ditiap tiap poli mengalami fluktuasi setiap bulannya periode Januari 2021 sampai dengan Desember 2021. Pelayanan Klinik Pratama Salbiyana harus dapat dijaga kualitasnya agar dapat memberikan pelayanan terbaik untuk dapat membantu tercapainya tujuan dan meningkatkan kualitas hidup pasien. Kepuasan pasien merupakan hal yang sangat penting dalam menilai kualitas pelayanan yang diberikan rumah sakit kepada pasiennya. Tingkat kepuasan pasien yang akurat sangat dibutuhkan dalam upaya peningkatan mutu layanan kesehatan. Oleh karena itu, pengukuran tingkat kepuasan pasien perlu dilakukan secara berkala, teratur, akurat, dan berkesinambungan. Dalam hal ini peneliti ingin menggunakan data mining klasifikasi untuk memprediksi kepuasan pasien terhadap sistem informasi manajemen Klinik Pratama Salbiyana. Teknik pengumpulan data dilakukan dengan observasi, studi literatur dan wawancara. Â Kata kunci: algoritma C4.5; data mining; tingkat kepuasan pasien